The role of ultrasound in venous thoracic outlet syndrome: Lesson based on a case report - Tiziana Vasile; Renato Farina; Pietro Valerio Foti; Antonio Basile (Journal of Medical Ultrasound, 2023)
Thoracic outlet syndrome is a rare neurovascular disease, usually caused by compression of subclavian vessels and/or brachial plexus by a cervical rib or hypertrophic scalene muscles. When the subclavian artery is compressed, it can cause perfusion deficiency with cyanosis and greater fatigue of the upper limb; if the subclavian vein is compressed, it can cause venous congestion with swelling and pain in the upper limb. When compression affects the brachial plexus, it can cause tingling or paresthesia of the upper limb. It can be mono or bilateral, congenital, or acquired. The diagnosis of vascular alterations is difficult due to the rarity, poor knowledge, and nonspecificity of symptoms. Ultrasound allows to localize and measure the vascular stenosis degree. Failure to diagnose can expose patients to serious health risks. We describe a rare case of venous compression caused by anterior scalene muscle hypertrophy.